Rich man, poor man, beggar man, thief: Accounting and the stigma of poverty. (March 2019) - Graham, Cameron; Grisard, Claudine
Abstract: In this paper, we examine the roles of accounting in two institutions dealing with poverty in Toronto during the 1920s. We draw on Georg Simmel's influential insights on poverty to explore how accounting for poverty alleviation programs helps structure the relationship between rich and poor in society. We argue that accounting serves to bridge the social distance between rich and poor while insulating the rich from the stigma of the poor. This enables the rich to benefit from their efforts to assist the poor, ensuring the legitimation of wealth and the continued existence of poverty. Our analysis of these two historical institutions helps us comprehend some of the roles of accounting in poverty alleviation today.